N-(4-Chlorophenyl)-4-methylpyridin-2-amine - Fairuz, Z.A.; Aiyub, Z.; Abdullah, Z.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(12)H(11)ClN(2), the dihedral angle between the benzene and pyridyl rings is 48.03 (8)degrees. Twists are also evident in the molecule, in particular about the N(a)-C(b) (a = amine and b = benzene) bond [C-N-C-C = -144.79 (18)degrees]. In the crystal, inversion dimers linked by pairs of N-H...N hydrogen bonds result in the formation of eight-membered {...NCNH}(2) synthons [or R (2) 2(8) loops]